THE GERMAN GOVERNMENT POLICY ON THE INTEGRATION AND DEPORTATION OF AFRICAN MIGRANTS - Foday Yarbou (POLITICO, 2022)
Migration from Africa to Europe and Germany is a complex and controversial phenomenon with major socioeconomic impacts on countries. The phenomenon reached an unprecedented level at the dawn of the 21st century hitting records globally. Migration in Africa has been preoccupied and shaped by pre-colonial, colonial, and post-colonial eras. The Trans-Atlantic slave trade is a typical example of this which shows the movement of millions of Africans to America and Europe in particular. To migrate means to move from one settlement to the other and this movement is always guided by policies and regulations. The stay of African migrants in Germany has both advantages and disadvantages. German policy on the integration and deportation of African migrants is well outlined and discussed in the work. Evidence shows that the country’s migrant policy comprises a set of rules and regulations that respect humanity and order.  The author discussed the key main policies on integration and deportation and propose some recommendations to the German policymakers. This work used a qualitative research method to build a convincing chain of evidence, which entails the exploration of scholarly works such as books, journal articles, newspapers, magazines, etc. However, in this paper, only field notes and secondary data are utilized. Furthermore, theoretical analysis and approaches are also used.